Exploring effects of Souvenaid on cerebral glucose metabolism in Alzheimer's disease - Nienke M.E. Scheltens; Casper T. Briels; Maqsood Yaqub; Frederik Barkhof; Ronald Boellaard; Wiesje M. van derFlier; Lothar A. Schwarte; Charlotte E. Teunissen; Amos Attali; Laus M. Broersen; Bart N.M. vanBerckel; Philip Scheltens (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Alzheimer's disease (AD) is associated with synapse loss. Souvenaid, containing the specific nutrient combination Fortasyn Connect, was designed to improve synapse formation and function. The NL‐ENIGMA study explored the effect of Souvenaid on synapse function in early AD by assessing cerebral glucose metabolism (CMRglc) with 18F‐fluorodeoxyglucose ([18F]FDG) positron emission tomography (PET). Methods We conducted an exploratory double‐blind randomized controlled single‐center trial. Fifty patients with mild cognitive impairment or mild dementia with evidence of amyloid pathology (cerebrospinal fluid or PET) were stratified for MMSE (20–24 and 25–30) and randomly 1:1 allocated to 24‐week daily administration of 125 mL Souvenaid (n = 25) or placebo (n = 25). Dynamic 60‐minute [18F]FDG‐PET scans (21 frames) with arterial sampling were acquired at baseline and 24 weeks. CMRglc was estimated by quantitative (Ki) and semiquantitative (standardized uptake value ratio, reference cerebellar gray matter) measurements in five predefined regions of interest and a composite region of interest. Change from baseline in CMRglc was compared between treatment groups by analysis of variance, adjusted for baseline CMRglc and MMSE stratum. Additional exploratory outcome parameters included voxel‐based analyses by Statistical Parametric Mapping. Results No baseline differences between treatment groups were found (placebo/intervention: n = 25/25; age 66 ± 8/65 ± 7 years; female 44%/48%; MMSE 25 ± 3/25 ± 3). [18F]FDG‐PET data were available for quantitative (placebo n = 19, intervention n = 18) and semiquantitative (placebo n = 20, intervention n = 22) analyses. At follow‐up, no change within treatment groups and no statistically significant difference in change between treatment groups in CMRglc in any regions of interest were found by both quantitative and semiquantitative analyses. No treatment effect was found in the cerebellar gray matter using quantitative measures. The additional Statistical Parametric Mapping analyses did not yield consistent differences between treatment groups. Discussion In this exploratory trial, we found no robust effect of 24‐week intervention with Souvenaid on synapse function measured by [18F]FDG‐PET. Possible explanations include short duration of treatment.